2014
DOI: 10.1186/1471-2466-14-122
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin inhibits airway eotaxin-1 induction and epithelial apoptosis through modulating oxidative stress-responsive MAPK signaling

Abstract: BackgroundEotaxin proteins are a potential therapeutic target in treating the peribronchial eosinophilia associated with allergic airway diseases. Since inflammation is often associated with an increased generation of reactive oxygen species (ROS), oxidative stress is a mechanistically imperative factor in asthma. Astragalin (kaempferol-3-O-glucoside) is a flavonoid with anti-inflammatory activity and newly found in persimmon leaves and green tea seeds. This study elucidated that astragalin inhibited endotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 33 publications
5
52
0
Order By: Relevance
“…The compound 5 has shown its promising and consistent cytotoxic activity in almost all cell lines (PC-3, HeLa, HCT-116, HEK-293 and MCF-7) tested within an IC 50 concentration range of 208-291 nM ( Table 1). The other potent molecules 3 [29], 4 [30] and 9 [31] were well studied for their various biological activities and cytotoxic potential that fully complies with our data in Table 1. Further, 5 was found to be more active against breast cancer MCF-7 cells with an IC 50 value of 208 nM in comparison to 1 (3.2 lM), indicating a 15-fold more potency than 1 (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The compound 5 has shown its promising and consistent cytotoxic activity in almost all cell lines (PC-3, HeLa, HCT-116, HEK-293 and MCF-7) tested within an IC 50 concentration range of 208-291 nM ( Table 1). The other potent molecules 3 [29], 4 [30] and 9 [31] were well studied for their various biological activities and cytotoxic potential that fully complies with our data in Table 1. Further, 5 was found to be more active against breast cancer MCF-7 cells with an IC 50 value of 208 nM in comparison to 1 (3.2 lM), indicating a 15-fold more potency than 1 (Fig.…”
Section: Resultssupporting
confidence: 89%
“…BEAS-2B cells were grown to 80-85% confluence at 37°C in an atmosphere of 5% CO 2 . LPS at the concentration of 1-2 lg/ml was applied to BEAS-2B cells for up to 12 h [21]. In another set of experiment, EGCG at a concentration of 100 lM was also added to the culture to analyse its cytoprotective role against LPS-induced toxicity [22].…”
Section: Cell Line and Treatmentmentioning
confidence: 99%
“…Astragalin, a bioactive component isolated from Rosa agrestis, has been reported to have various pharmacological activities including anti-inflammatory and antioxidant effects [10,11]. It has been reported that astragalin inhibited iNOS and COX-2 expression in macrophages [11].…”
Section: Introductionmentioning
confidence: 99%